Non-contacting Busbars for Advanced Cell Structures Using Low Temperature Copper Paste. (April 2015) - Wood, Don; Kuzma-Filipek, Izabela; Russell, Richard; Duerinckx, Filip; Powell, Nick; Zambova, Adriana; Chislea, Brian; Chevalier, Pierre; Boulord, Caroline; Beucher, Alexandre; Zeghers, Nicolas; Szlufcik, Jozef; et al.
Abstract: We report the use of a screen-printable copper paste to form the front busbars on high efficiency photovoltaic cell structures in combination with copper fingers formed by light induced plating. Such a process route offers economic benefits relative to the fully plated front metallization due to the reduced requirement for laser ablation and increased cell performance. We demonstrate improved open circuit voltage and fill factor compared to cells that used plating for both the fingers and the busbars. These result from reduced contact between the semiconductor and the metal and from reduced shunting compared to the laser ablated and plated electrodes. p-type 'PERC' cells have been fabricated with copper plated fingers and screen-printed copper busbars with a median cell efficiency of 20.4%, compared to 20.3% for those with fully plated busbars. n-type 'PERT' cells reached a cell efficiency of 20.9% for both front metallization schemes. The screen-printed busbars gave a ∼5 mV advantage over the plated busbars in both cases.